Effect of firing temperatures on phase formation and microstructure of Ba(Zr0.3Ti0.7)O3 ceramics prepared via mixed oxide method - Bongkarn, Theerachai; Phungjitt, Nalinee; Vittayakorn, Naratip (My University, 2009)
Ba(Zr0.3Ti0.7)O3 (BZT) ceramics were fabricated by a mixed oxide synthetic route. The effect of calcination and sintering temperatures on phase formation and the microstructure of the ceramics were investigated. The pure perovskite phase of BZT powders was obtained with a calcination condition of 1300°C for 4 h. The sintered pellets showed a pure peroverskite cubic phase in all samples. The microstructure of the powders exhibited an almost-spherical morphology and had a porous agglomerated form. The average particle sizes and the average grain sizes were increased from 0.2 to 1.1 μm and 3.9 to 25.1 μm with increasing calcination and sintering temperatures, respectively. The densest and the highest maximum dielectric constant was found in the BZT ceramic sintered at 1550°C. Copyright © Taylor & Francis Group, LLC.
Keywords: Barium zirconate titanate; Microstructure; Mixed oxide; Phase formation